2023
DOI: 10.1007/s40477-023-00823-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assessment of muscle mass and correlation with clinical outcomes in critically ill patients: a prospective observational study

Cristian Arvey Guzmán-David,
Héctor Andrés Ruiz-Ávila,
Diana Alexandra Camargo-Rojas
et al.

Abstract: Purpose Muscular atrophy implies structural and functional alterations related to muscular force production and movement. This condition has been reported to be the main reason for generalized muscle weakness; it reflects the severity of the disease and can have a profound impact on short- and long-term clinical outcomes. The purpose of this study was to determine whether muscle atrophy ultrasound parameters early predict muscle weakness, morbidity, or 28-days mortality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…A recent investigation in 37 critically ill subjects, 24 of whom developed ICU-acquired weakness, found that the changes in the thickness and CSA of various skeletal muscles between admission and the 10th day of ICU stay was associated with the development of weakness with areas under the ROC curves between 0.734 and 0.888 [ 92 ]. A subsequent study in 31 critically ill patients confirmed how a decrease in rectus femoris CSA > 10% during the first 72 h after ICU admission increased the risk for limb muscle weakness and handgrip weakness [ 105 ]. A recent systematic review and meta-analysis that included chronic as well as acutely ill subjects (including critically ill patients) found that muscle thickness, CSA, and echo-intensity have been shown to be correlated with functional outcomes such as muscle strength, physical function, exercise tolerance, and quality of life [ 106 ].…”
Section: Ultrasonographic Assessment Of Muscle Weaknessmentioning
confidence: 99%
“…A recent investigation in 37 critically ill subjects, 24 of whom developed ICU-acquired weakness, found that the changes in the thickness and CSA of various skeletal muscles between admission and the 10th day of ICU stay was associated with the development of weakness with areas under the ROC curves between 0.734 and 0.888 [ 92 ]. A subsequent study in 31 critically ill patients confirmed how a decrease in rectus femoris CSA > 10% during the first 72 h after ICU admission increased the risk for limb muscle weakness and handgrip weakness [ 105 ]. A recent systematic review and meta-analysis that included chronic as well as acutely ill subjects (including critically ill patients) found that muscle thickness, CSA, and echo-intensity have been shown to be correlated with functional outcomes such as muscle strength, physical function, exercise tolerance, and quality of life [ 106 ].…”
Section: Ultrasonographic Assessment Of Muscle Weaknessmentioning
confidence: 99%